Emergence of the Era of the Qualified Merchant Scientifically and professionally: A Comparative Study (Al-Mostansiriyah journal for Arab and international studies, 2026)
Abstract: The scientific and technological developments is casting its shadow on realities of some pieces of commercial legislation, by dictating that a merchant should be eligible scientifically and be subjected to an adequate train in order to be qualified to grant a license for exercising some sorts of trade. The supervisory and control authorities are being binding by law to ascertain the provision of the aforesaid requirements in a merchant in exercising some sorts of trade, with a view of regarding certain considerations relating, i.e., modern commerce, electronic trade activities or consumer protection. This article is an attempt to investigate aforesaid legal requirements in the light of scarcity of legal literatures in dealing with this theme, and the ambiguity surrounding the determination of its scope, features, reasonability of their imposition, and to be expand all realms of commercial business. Keywords: merchant, qualification, training, experience,commercial work.